PENGARUH BRIEF CONSELING FARMASIS DALAM PENINGKATAN PERILAKU DAN KEPATUHAN MINUM OBAT DI RSUD ULIN BANJARMASIN - Saftia Aryzki; Amaliyah Wahyuni (Jurnal Insan Farmasi Indonesia, 2020)
Hypertension is one of the deadliest diseases in the world. As many as 1 billion people in the world or 1 in 4 adults suffer from this disease. Patient behavior by controlling the patient's blood pressure will help achieve the success of patient therapy. The purpose of this study was to determine the Brief Effect of Pharmacist Counseling in Improving Behavior and Adherence to at Ulin Hospital, Banjarmasin. The study was a quasi-experimental study using two groups. The sampling method was carried out by counsecutive sampling with simple random that met the inclusion and exclusion criteria. The sample in this study was 60 samples with 30 samples from the control group and 30 samples from the intervention group. This research was conducted at the Internal Medicine Polyclinic at Ulin Hospital from March-June 2020. The data collection technique used in this study was a questionnaire on the level of treatment behavior, the MMAS (Morisky Medication Adherence Scale) and EQ5D (Euro Quality of Life) compliance questionnaire. The results of this study were brief pharmacist counseling in improving behavior, medication adherence and the results of hypertension therapy at RSUD Ulin Banjarmasin which had a positive effect on the intervention group.